2019
DOI: 10.3389/fnins.2019.00986
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of CRH From GABAergic Forebrain Neurons Promotes Stress Resilience and Dampens Stress-Induced Changes in Neuronal Activity

Abstract: Dysregulation of the corticotropin-releasing hormone (CRH) system has been implicated in stress-related psychopathologies such as depression and anxiety. Although most studies have linked CRH/CRH receptor 1 signaling to aversive, stress-like behavior, recent work has revealed a crucial role for distinct CRH circuits in maintaining positive emotional valence and appetitive responses under baseline conditions. Here we addressed whether deletion of CRH, specifically from GABAergic forebrain neurons (CrhCKO–GABA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 108 publications
(168 reference statements)
6
31
0
Order By: Relevance
“…In contrast, either CRF-R1 or CRF-R2 activation (or both) was sufficient to enhance long-term plasticity (Fig.4h,-i). Our data supports CRF as a positive regulator of synaptic transmission, in agreement with other reports describing CRF generally as a facilitator of excitatory neurotransmission throughout different brain regions (31,55,73,74).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, either CRF-R1 or CRF-R2 activation (or both) was sufficient to enhance long-term plasticity (Fig.4h,-i). Our data supports CRF as a positive regulator of synaptic transmission, in agreement with other reports describing CRF generally as a facilitator of excitatory neurotransmission throughout different brain regions (31,55,73,74).…”
Section: Discussionsupporting
confidence: 93%
“…To confirm our direct stress response in the hippocampus we performed in situ hybridization analysis for immediate early genes crh and cfos . (5355), in mice 20 minutes after being subjected to FS. We observed a local increase of crh and cfos mRNA expression in the CA1 PC layer (Fig.1h-i), demonstrating an upregulation of immediate early genes in the CA1 PC layer directly after acute stress.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed the absence of Crh in the GABAergic neurons by expression mapping in Crh CKO-GABA mice. This absence of Crh from the forebrain GABAergic neurons resulted in social interaction deficits in mice, suggesting the role of CRH in the regulation of social behavior in neuropsychological disorders such as PTSD [89]. The Crh CKO-GABA mice displayed a resilient phenotype upon exposure to chronic social defeat stress accompanied by a stress-induced expression of c-fos and zif268 genes in several regions of the brain.…”
Section: Genetics Of Neuronal/functional Changes In Ptsdmentioning
confidence: 98%
“…Stress is a major contributor to the etiology of anxiety and depression (Dedic et al, 2019). We used the EPM and OFT to evaluate the effects of CRS on anxiety-like behavior in pups in FIGURE 1 | Effect of PS on embryo development.…”
Section: Effect Of Ps On Behavior In Adolescencementioning
confidence: 99%